Extrafacial Granuloma Faciale: A Case Report and Brief Review - Jacqueline Deen; Thomas P. Moloney; Jim Muir (Karger Publishers, 2017)
Granuloma faciale (GF) is a rare, inflammatory, cutaneous disorder of unknown aetiology. It presents clinically as one or several well-circumscribed violaceous papules, plaques, and nodules almost exclusively confined to the facial region. Rarely, extrafacial lesions can occur, most often on sun-exposed sites. We report a case of extrafacial GF in a 63-year-old male with indolent lymphoma, who presented with plaques involving the right preauricular region and left posterior axilla. The clinical and histopathological findings were consistent with GF. Our case highlights the importance of performing skin biopsies in patients with persistent erythematous plaques and nodules, particularly to exclude important malignant and granulomatous differential diagnoses.